IN VITRO ESTABLISHMENT OF SYMBIOSIS IN ACROPORA MILLEPORA PLANULAE - van Oppen (My University, 2001)
All reef-building corals form obligate endosymbioses with dinoflagellates (zooxanthellae) belonging to the genus Symbiodinium. Most of these, however, produce azooxanthellate eggs and planula larvae (Fadlallah 1983: Harrison and Wallace 1990; Richmond and Hunter 1990). Hence, these corals are dependent on repeated (i.e. every generation) uptake ofzooxanthellae from the environment. In some species symbiont acquisition is possible during the planula stage (Schwarz et al. 1999), but in others establishment of symbiosis does not take place until after metamorphosis and settlement (Babcock and Heyward 1986).